Rhizobacteria From Root Nodules of an Indigenous Legume Enhance Salinity Stress Tolerance in Soybean - Ilangumaran, Gayathri; Schwinghamer, Timothy Damian; Smith, Donald Lawrence (Frontiers in Sustainable Food Systems, 2021)
Soybean is the most widely grown legume worldwide, but it is a glycophyte and salinity stress can decrease its yield potential up to 50%. Plant growth promoting rhizobacteria (PGPR) are known to enhance growth and induce tolerance to abiotic stresses including salinity. The aim of this study was to isolate such PGPR from the root nodules of Amphicarpaea bracteata, a North American relative of soybean. Isolated strains were identified, and 15 strains were screened for potential utilization as PGPR of soybean through a series of greenhouse trials. Four isolates that greatly improved shoot and root growth were further selected and screened under a range of salt concentrations. Two of the most promising strains, Rhizobium sp. SL42 and Hydrogenophaga sp. SL48 were ascertained to exert the greatest beneficial effects on soybean growth and salinity tolerance. They were co-inoculated with Bradyrhizobium japonicum 532C (Bj) and the plants were grown up to the harvest stage. The treatment of Bj+SL42 resulted in higher shoot biomass than the control, 18% at the vegetative stage, 16% at flowering, 7.5% at pod-filling, and 4.6% at harvest and seed weight was increased by 4.3% under salt stress (ECe =7.4 ds/m). Grain yield was raised in Bj+SL48 and Bj+SL42+SL48 by 7.4% and 8.1%, respectively under optimal conditions. Nitrogen assimilation and shoot K+/Na+ ratio were also higher in the co-inoculation treatments. This study suggested that inoculation with bacteria from an indigenous legume can induce stress tolerance, improve growth and yield to support sustainability, and encourage ecological adaptability of soybean.